2023
DOI: 10.1002/vetr.3169
|View full text |Cite
|
Sign up to set email alerts
|

‘Bowls are boring’: Investigating enrichment feeding for pet dogs and the perceived benefits and challenges

Madeline Heys,
Imogen Lloyd,
Carri Westgarth

Abstract: BackgroundCanine enrichment feeding (CEF) is recommended by canine professionals, yet research into its use by dog owners is absent. This study is the first to investigate who uses CEF and the perceived benefits and barriers.MethodsA cross‐sectional survey advertised in July and August 2021 received 1750 usable responses about owner and dog demographics, feeding methods used, canine quality of life and behaviour (Mini‐Canine Behavioural Assessment and Research Questionnaire [C‐BARQ]).ResultsKongs, chews and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This is highlighted by Hubrecht [28], who found dogs who received enrichment spent significantly less time inactive-though subjects spent 51% of their time inactive before the intervention (quite different from companion dog populations). Additionally, Heys et al [27] emphasized the human perception of toys' effects on their dogs. Humans who use food-based toys were more likely to report more appetitive behaviors during feeding time in their dogs and less undesirable food-seeking behaviors such as begging.…”
Section: Measuring Welfare: Appetite and Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…This is highlighted by Hubrecht [28], who found dogs who received enrichment spent significantly less time inactive-though subjects spent 51% of their time inactive before the intervention (quite different from companion dog populations). Additionally, Heys et al [27] emphasized the human perception of toys' effects on their dogs. Humans who use food-based toys were more likely to report more appetitive behaviors during feeding time in their dogs and less undesirable food-seeking behaviors such as begging.…”
Section: Measuring Welfare: Appetite and Activitymentioning
confidence: 99%
“…For dogs, specially designed retail toys are common sources of stimulation. A recent survey-based study on companion dogs found many people believe feeding enrichment toys provide mental stimulation and prevent boredom in dogs [27]. Dog toys are widely touted to improve dogs' well-being through facilitating natural exploratory behavior and mitigating stress-related, maladaptive behaviors such as over-grooming and destruction of furniture [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary method of feeding uses a stainless bowl. This conventional feeding technique is boring [11], does not sufficiently mimic natural behavior, and may be related to obesity [12,13]. In free-roaming dogs, food sources such as carcasses require considerable eating time, approximately 26 min [14].…”
Section: Introductionmentioning
confidence: 99%